2021
DOI: 10.1371/journal.pone.0260744
|View full text |Cite
|
Sign up to set email alerts
|

Trend in blood lead levels in Taiwanese adults 2005–2017

Abstract: This study examined the trend of blood lead levels (BLLs) in Taiwanese adults and analyzed the variations in the BLL between Linkou (northern) and Kaohsiung (southern) hospital branches. Between 2005 and 2017, 3,804 adult participants received blood lead tests at the Linkou (n = 2,674) and Kaohsiung (n = 1,130) branches of Chang Gung Memorial Hospital. The geometric mean of BLL was 2.77 μg/dL. The adult participants from the Kaohsiung branch were not only age older (49.8±14.1 versus 39.4±14.2 years; P<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Taiwan had banned the use of leaded petrol in road vehicles since 2000 and the lower blood lead level population was obtained from the further study which revealed that geometric mean of blood lead in pregnant women, cord blood and children at 2-3, 5-6 and 8-9 years old were 2.21, 1.30, 2.48, 2.49 and 1.97 µg/dl, respectively (Huang et al 2012). These results reveal blood lead levels in Taiwan residents were not higher than in most developed and developing countries (Brody et al 1994;Liou et al 1994;Liou et al 1996), however, the blood lead level of individuals living in southern Taiwan was still higher than the mean blood lead level in Taiwan (Fang et al 2021). We hypothesis that lead which intake from inhalation, ingestion, and skin could do harm to our respiratory system and ultimately induce lung brotic change.…”
Section: Introductionmentioning
confidence: 68%
“…Taiwan had banned the use of leaded petrol in road vehicles since 2000 and the lower blood lead level population was obtained from the further study which revealed that geometric mean of blood lead in pregnant women, cord blood and children at 2-3, 5-6 and 8-9 years old were 2.21, 1.30, 2.48, 2.49 and 1.97 µg/dl, respectively (Huang et al 2012). These results reveal blood lead levels in Taiwan residents were not higher than in most developed and developing countries (Brody et al 1994;Liou et al 1994;Liou et al 1996), however, the blood lead level of individuals living in southern Taiwan was still higher than the mean blood lead level in Taiwan (Fang et al 2021). We hypothesis that lead which intake from inhalation, ingestion, and skin could do harm to our respiratory system and ultimately induce lung brotic change.…”
Section: Introductionmentioning
confidence: 68%
“…Taiwan had banned the use of leaded petrol in road vehicles since 2000 and the lower blood lead level population was obtained from the further study which revealed that geometric mean of blood lead in pregnant women, cord blood and children at 2-3, 5-6 and 8-9 years old were 2.21, 1.30, 2.48, 2.49 and 1.97 µg/dl, respectively (Huang et al 2012). These results reveal blood lead levels in Taiwan residents were not higher than in most developed and developing countries (Brody et al 1994;Liou et al 1994;Liou et al 1996), however, the blood lead level of individuals living in southern Taiwan was still higher than the mean blood lead level in Taiwan (Fang et al 2021). We hypothesis that lead which intake from inhalation, ingestion, and skin could do harm to our respiratory system and ultimately induce lung brotic change.…”
Section: Introductionmentioning
confidence: 68%
“…Brain extracellular space constitutes 15-30% of the brain volume and brain vasculature 3% of the brain volume [51]. Increased size of human brain from 400 cm 3 to 1200 cm 3 [52] indicates increased cognition capacity of modern human. Serum creatinine 0:88 AE 0:2 mg=dl ðÞ has been reported for human with blood lead level of 2:36 À 2:54 μg=dl [53].…”
Section: Discussionmentioning
confidence: 99%